Implementation Gifford Method For Digital Image Security - Fauduziduhu Laia; Erwin Panggabean (Information Technology and Science (ITScience), 2020)
Rapid development of digital image technology secret causes images require security aspect. Reviews These digital secret image can be encrypted using cryptographic methods. After being encrypted, the image is randomized, so that if it is Obtained by an unauthorized party, the image has no meaning. The cryptographic algorithm used in this study is Gifford method. The Gifford method is a stream cipher, a symmetry encryption algorithm that transforms the data character by character. Gifford has 8 registers filled with key bits. The processes performed by the Gifford method are the Output Function process, the 1-bit Sticky Shift Right process, the 1-bit Left Shift process, the XOR operation and the shift register operation to the right. The decryption process must use the same key as the encryption process in order to Obtain the original image.